Assessing the Key Success if Ar Rahnu Usage in Malaysia - Azim, Zainal Azhar b Zainal; Ghazali, Amirul Syafiq bin Mohd; Mohamed, Juliza; Kassim, Aza Azlina bt Md; Hussain, Hafezali Iqbal (International Journal of Engineering and Technology, 2018)
Ar Rahnu means pledge or pawn. Rahn is a contract of security. One of the objectives of Ar Rahnu is to develop the economics of Ummah (person who pawn their property/asset). While this concept had been practising until today, many customers tend to use the services for their personal consumption and contingency expenditure. Therefore, the objective of the study is to analyse the factors that might influence personal consumption and investment usage. Multi dependent variables are used in order to identify the relationship between the factors of usage towards personal consumption and investment. The method of structural equation modelling specifically a method of partial least square (PLS) was utilized in this study. From the model run by using PLS-SEM, the results revealed that people used Ar-Rahnu as an investment is contributed by customer service provided, location of the Ar-Rahnu services and also based on the Shariah view with 48% of variation. While, the customer uses Ar-Rahnu for personal consumption due to the factor of customer service and Shariah view with 39.7% of variation. The result might benefit the regulator in finding a new alternative to develop the socio economic of society through Islamic product and principle.